"Digital Rush": In Search of Balance between Professional and Market Logics in Web Journalism - Bogomazova, Liudmila (Journal of Economic Sociology, 2021)
A book written by French-born American sociologist Angele Christin, Metrics at Work: Journalism and the Contested Meaning of Algorithms, is devoted to the specificities of the functioning of publications during the traffic-chase era. The book’s main goal is to show how the implementation of algorithms affects the professional identity and working practices of journalists. The scholar uses a multi-stage theoretical framework as she turns to Bour- dieu’s concept of field, the sociology of "Worlds" by Boltanski and Thevenot, the theory of institutional isomorphism proposed by DiMaggio and Powell, and other relevant approaches examined in The New Economic Sociology. The book is based on a comparative study of two web publications in the United States and France during the period 2011-2015. The author uses a mixed methodology whose core is comprised of observation and semi- structured interviews with the staff of media organizations. Referring to the broad empirical material, Christin wonders whether metrics are really able to eradicate dis-tinctions between national mass media in different countries. Although the two web publications face similar challenges in terms of modern journalism, they tackle them in different ways. This is due to the embeddedness of the professional activity of journalists in the institutional context, organizational structures, and profes-sional fields. The review raises the key issues of the book: a brief history of the formation of web journalism in the United States and France, the media organizations’ perception of metrics and audience, and the role of independent professionals in news production.